1983
DOI: 10.1007/bf03188745
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent pharmacokinetics of sulpirideand sulpiride-induced prolactin secretionin man

Abstract: Sulpiride (SU), a widely used benzamide neuroleptic, is known to promote rapid prolactin release. Sulpiride plasma level and the prolactin response to the most commonly used dose, i.e., 50 and 200 mg sulpiride (administered orally), were studied in ten male volunteers.The design of this study permitted the simultaneous measurement of the sulpiride plasma level for 48 hours, by means of a new HPLC-electrochemical detection method, and of the prolactin level, by means of RIA.Pharmacokinetic study of sulpiride sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
2
7
0
2
Order By: Relevance
“…The peak plasma prolactin levels (Cmax,PRL) have been reported to be dose-related up to a maximal release following administration of remoxipride [13,14,29], sulpiride [16,[21][22][23][24][25] and also following TRH [26,27]. Maximal prolactin peak concentrations are expected to be achieved with the doses of remoxipride and TRH administered in the present study [26,27].…”
Section: Introductionmentioning
confidence: 59%
“…The peak plasma prolactin levels (Cmax,PRL) have been reported to be dose-related up to a maximal release following administration of remoxipride [13,14,29], sulpiride [16,[21][22][23][24][25] and also following TRH [26,27]. Maximal prolactin peak concentrations are expected to be achieved with the doses of remoxipride and TRH administered in the present study [26,27].…”
Section: Introductionmentioning
confidence: 59%
“…In a nutshell, there is a dose-dependent biphasic action that relates to the balance of pre- to postsynaptic effects (50 mg > 200 mg presynaptic vs. 400 mg postsynaptic predominance). In addition, pharmacokinetic data showed that within the tuberoinfundibular system the maximal prolactin response to 50 and 200 mg are time shifted (Sugnaux et al, 1983): the response to 50 mg sulpiride occurrs1 h later compared to 200 mg. Thus, postsynaptic effects rush in or dominate later in time for low compared to high doses.…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, a decreased striatal activation to reward seen with 400 mg sulpiride is in keeping with the hypothesis that inhibition of dopamine transmission (via postsynaptic effect) predominates 400 mg sulpiride (McCabe et al, 2011). In addition, the maximal prolactin response to 50 and 200 mg are time shifted (Sugnaux et al, 1983): the response to 50 mg sulpiride occurred 1 h later compared to 200 mg. Thus, the postsynaptic effects dominate later in time for low compared to high doses and consequently, presynaptic effects had to peak earlier in time for high compared to low doses.…”
Section: Methodsmentioning
confidence: 99%
“…Dose selection was based on previous, similar studies showing behavioral effects at similar (and lower) doses using the same drugs in healthy volunteers (Mehta et al, 1999(Mehta et al, , 2000Volkow et al, 2002). The timing of fMRI testing was performed at approximately the time of maximal plasma levels of both drugs based on pharmacokinetic data (Sugnaux et al, 1983;Wagstaff et al, 1994;Kimko et al, 1999).…”
Section: Methodsmentioning
confidence: 99%